Thermal and compositional characterization of chicken, beef, and pork cartilage to establish its lifetime (2023)
The thermal behavior of commercial chicken, beef, and pork cartilage, were studied using thermal analysis techniques. We use thermogravimetry (TGA) to study their thermal stability between room temperature and 500 °C; differential scanning calorimetry (DSC) in a temperature range between - 50 °C and 300 °C to determine their phase changes associated with endothermic or exothermic processes, and mass spectrometry coupled to TGA to determine the release of elements as they are heated; the results are similar for the three samples. In the thermogravimetric analysis, three different phases were found corresponding to the stages of dehydration (21 °C < T < 100 °C), decomposition (100 °C < T < 300 °C, and degradation (300 °C < T < 500 °C). The DSC study shows two endothermic anomalies corresponding to melting of the aqueous content (−25 °C < T < 25 °C) and evaporation of the aqueous content (27 °C < T < 175 °C), with required enthalpies of 137.30 J/g and 1193 J/g, respectively. Mass spectrometry evidenced the release of molecules such as nitrogen, oxygen, carbon dioxide, and calcium. This study intends to give an approximation to the possible behavior of commercial cartilage that is stored for use in surgery, in no way is it intended to simulate the behavior within the human body, since the biological and physicochemical parameters inside the body are not studied. From the TGA results for different heating rates, we calculated the activation energies required in each of the phases, whose values are 3250,95 J/mol in the dehydration stage, 5130,63 J/mol for decomposition, and 22,677,52 J/mol for degradation. With the activation energies and following the Toops theory (TOOP, 1971) [13], we proceeded to calculate the lifetime in the completion of the three stages or what in thermogravimetric analysis, is known as useful life per stage, finding that a sample of cartilage stored under ambient conditions, after 62 days it loses its initial properties. Which provides an important parameter for the storage of possible synthetic biomaterials with properties similar to cartilage. It is clear that here the useful life or the change of the original properties due to temperature effects is studied, which under the Arrhenius theory is transferred to the kinetic study over time